STUDI LITERATUR: REMOTE AUDIT - Nabila Febriyana; Sindy Utami; Vivi Armadhani; Madaniyah Nur Aisyah Putri; James Christian; Tri Ratnawati (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
This study aims to determine the effects and advantages and disadvantages of using the remote audit method during the Covid 19 pandemic and the development of remote audits after the Covid 19 pandemic. This research uses the Literature Study method in which all data is obtained from the results of previous studies. Internal audit work practices have been affected by the implementation of the PSBB and the ban on face-to-face interactions due to the Covid-19 pandemic. Companies use remote audit techniques or remote audits to overcome this problem. With the use of digital technology, audits can be carried out from abroad. Remote Audit has advantages and disadvantages, but using information technology makes the audit process easier. In addition, remote audits are used to find and thwart fraud in pandemic situations. Auditor processes had to be modified extensively in these circumstances, and information technology had to be used to assist remote auditing. Overall, remote auditing is a useful alternative for conducting audits during the Covid-19 pandemic.